Obesity as Predictor of Mortality of Colorectal Cancer: an Evidence-based Case Report - Matthew Billy; Hasna Sholihah; Kiwah Andanni; Margareth Ingrid Anggraeni; Saur M.E.J. Siregar; Listya Tresnanti Mirtha (Acta Medica Indonesiana, 2016)
Aim: to determine all-cause mortality and cancer-spesific mortality of colorectal cancer patient with obesity. Methods: a search was conducted on Pubmed, Proquest, Ebsco, Scopus, and Cochrane based on clinical query. The screening of title and abstract using inclusion and exclusion criteria, filtering double, and reading full text led to one useful article. This study, which is meta-analysis was critically appraised for its validity, importance and applicability. Results: the relative risk of colorectal cancer patient with pre-existing obesity having cancer-specific mortality and all-cause mortality is 1.22 (95% CI, 1.003-1.35) and 1.25 CI (95% CI, 1.14-1.3) respectively, when compared with non-obese colorectal cancer patient. Conclusion: pre-existing obesity is related to increased risk of all-cause mortality and cancer-spesific mortality of in colorectal patient. Control of body weight is recommended in this patient through combination of diet, physical activity, behavior therapy, pharmacotherapy, and surgery.